From compliance to co-production: Emergent forms of agency in Sustainable Wine Production in New Zealand. (December 2017) - Rosin, Christopher J; Legun, Katharine A; Campbell, Hugh; Sautier, Marion
This article engages with non-human agency through the interrogation of the emerging role of metrics in the governance of sustainability in the New Zealand primary sector. In it, we argue that the agency of the metrics builds on previous work that has elaborated the impact of audited best practice on the subjectivities of producers and processors, including the recent examination of the active influence of metrics that engenders unexpected and uncontrolled change in social networks of production. In this case, the analysis of the influence of metrics shifts to those used within a recently introduced 'learning' tool (Wine Industry Sustainability Engine) that can be classified as an effort in transition management. The capacity of metrics as agents is already apparent in the perceived interactions and engagements with the Wine Industry Sustainability Engine tool as expressed by likely users during assessments of the usability of initial pilot software. Using their response, we demonstrate that, despite intentions to use the tool to foster particular sets of practices and ethics through benchmarking, the metrics have multiple roles in production worlds—compelling compliance to regulations, creating new ways to communicate complex relations and practices, and generating information for reflexive self-evaluation. Through these roles, we argue, metrics clearly operate as both a material and ontological non-human actor, expressed in different ways in different assemblages. This conclusion has implications for the application of transition management more broadly, and helps us to better understand what we want metrics to accomplish, what they can accomplish, and the possible gap between the two.